Geographical Analysis of the Determinants of Spatial Expansion in the City of Kirkuk (Raparin Journal of Humanities (RJH), 2021)
The city of Kirkuk found a large spatial expansion in line with its functional requirements. It was interrupted by determinants represented by the stress areas that clearly affected the city’s growth. Based on that, the research aims to classify the stress areas and identify axes and directions for their expansion, relying on an inductive approach.  Introduction, the first axis began to study the stress areas in terms of their concept, classification and characteristics, while the second axis was devoted to the school of urban development (population and urbanism) by dividing them into four morphological stages, while the third axis was devoted to studying and identifying patterns of stress areas and their impact on spatial expansion, and the research was concluded with a sentence of  Conclusions and recommendations.